2016
DOI: 10.1017/s1368980016000525
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity predicts dietary quality regardless of season in 6–12-month-old infants in south-west Ethiopia

Abstract: Objective: Simple, cost-effective and convenient instruments like food groupbased scores are proposed to assess micronutrient adequacy of children in developing countries. We assessed the predictive ability and seasonal stability of a dietary diversity score (DDS) to indicate dietary quality of infants. Design: A 24 h dietary recall assessment was carried out on a sample of 320 and 312 breast-fed infants aged 6-12 months during harvest (HS) and pre-harvest (PHS) seasons, respectively, in Ethiopia. DDS was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…We previously found that children who consumed ≤2 food groups were likely to have inadequate micronutrient intake [15]. In the present analysis, the odds of being stunted was significantly higher for those who consumed ≤2 food groups in the previous 24 h. This was observed both among children in the HS and in the pooled data.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…We previously found that children who consumed ≤2 food groups were likely to have inadequate micronutrient intake [15]. In the present analysis, the odds of being stunted was significantly higher for those who consumed ≤2 food groups in the previous 24 h. This was observed both among children in the HS and in the pooled data.…”
Section: Discussionsupporting
confidence: 62%
“…To our knowledge, no study has examined the impact of seasonality on these associations. Previously, we found an association of DDS with mean micronutrient density adequacy (MMDA) and the association proved to be stable over two distinct seasons in Southwest Ethiopia [15]. Moreover, having a DDS ≤ 2 was associated with an inadequate intake of micronutrients.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…15 Previous studies in pastoral communities also reported low dietary diversity with dairy and cereals being the major food groups. 3,5,24,25 Similarly, such low levels of dietary diversity scores have been previously reported from different parts of Ethiopia: 2.2 by Arimond and Ruel, 26 2.2 by Beyene et al 27 and 2.1-2.3 by Wondafrash et al 28 Hirvonen 29 also compared dietary diversity in Ethiopia Abbreviations: RNI, recommended nutrient intake; MAR, mean nutrient adequacy ratio; NAR, nutrient adequacy ratio (%).…”
Section: Discussionmentioning
confidence: 66%